A Network-Based Approach to Explore the Mechanism and Bioactive Compounds of Erzhi Pill against Metabolic Dysfunction-Associated Fatty Liver Disease - Shaojie Huang; Fei Mu; Fei Li; Wenjun Wang; Haixia Chen; Lu Lei; Yang Ma; Yi Ding; Jingwen Wang (Journal of Diabetes Research)
Erzhi pill (EZP), a classical traditional Chinese medicine prescription, exerts a potent hepatoprotective effect against metabolic dysfunction-associated fatty liver disease (MAFLD), previously known as nonalcoholic fatty liver disease (NAFLD). However, the mechanism and bioactive compounds underlying the hepatoprotective effect of EZP have not been fully elucidated. In this study, a systematic analytical platform was built to explore the mechanism and bioactive compounds of EZP against MAFLD. This was carried out through target prediction, protein-protein interaction (PPI) network construction, gene ontology, KEGG pathway enrichment, and molecular docking. According to the topological parameters of the PPI network, compound-target-pathway network, 9 targets, and 11 bioactive compounds were identified as core targets and bioactive compounds for molecular docking. The results showed that EZP exerts anti-MAFLD effects through a multicomponent, multitarget, multipathway manner, and luteolin and linarin may be the bioactive compounds of EZP. This study provides further research insights and helps explore the hepatoprotective mechanism of EZP.